1996
DOI: 10.1523/jneurosci.16-22-07206.1996
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term GDNF Treatment Provides Long-Term Rescue of Lesioned Nigral Dopaminergic Neurons in a Rat Model of Parkinson’s Disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) has been shown to exert neuroprotective effects on dopamine (DA) neurons in vivo. Here we report long-term rescue of nigral DA neurons after delayed short-term GDNF administration in a rat lesion model that reproduces the slowly progressing degenerative process seen in Parkinson's disease. GDNF injected close to the substantia nigra provided near-complete protection and persistent survival of the lesioned nigral neurons for at least 4 months after discontinuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
134
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(153 citation statements)
references
References 25 publications
17
134
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12] However, when GDNF is administered with a delay after the insult, sparing of DA neurons is only marginal and the magnitude of functional recovery probably reflects the number of DA neurons still surviving and maintaining nigrostriatal connections. 10,[23][24][25] In contrast with previous studies 10,26 in which three or four deposits of 6-OHDA were injected to create more extensive striatal lesions, 6-OHDA was injected at only one site in our model and less damage might have been incurred to nigrostriatal connections. Using adenoviral vectors Kozlowski et al 22 demonstrated that delivering GDNF gene to the SN 1 week after lesioning rescued DA neurons and increased the number of DA neurons maintaining a connection to the striatum.…”
Section: Discussionmentioning
confidence: 90%
“…[5][6][7][8][9][10][11][12] However, when GDNF is administered with a delay after the insult, sparing of DA neurons is only marginal and the magnitude of functional recovery probably reflects the number of DA neurons still surviving and maintaining nigrostriatal connections. 10,[23][24][25] In contrast with previous studies 10,26 in which three or four deposits of 6-OHDA were injected to create more extensive striatal lesions, 6-OHDA was injected at only one site in our model and less damage might have been incurred to nigrostriatal connections. Using adenoviral vectors Kozlowski et al 22 demonstrated that delivering GDNF gene to the SN 1 week after lesioning rescued DA neurons and increased the number of DA neurons maintaining a connection to the striatum.…”
Section: Discussionmentioning
confidence: 90%
“…Extremely promising pre-clinical [5][6][7][8] and open-label clinical trials [9][10][11] , confirming the neuroprotective role of GDNF on dopaminergic neurons, renewed enthusiasm that disease modulating approaches were within reach. Unfortunately, issues related to the delivery of GDNF undoubtedly contributed towards the failure to reach satisfactory clinical outcome measures in a double-blind placebo-controlled study where patients received intra-putamenal infusion of recombinant GDNF via implanted catheters 12, 13 .…”
Section: Text Introductionmentioning
confidence: 99%
“…The effects of GDNF have been studied in animal models of PD. Administered into the striatum or in the substantia nigra (SN) of rats, [3][4][5] GDNF has a neuroprotective effects for DA neurons after striatal lesions. In a primate model of PD, intracerebral injection of GDNF is followed by improved motor function.…”
Section: Introductionmentioning
confidence: 99%